Kemahiran Pelajar Melaksanakan Amali Elektronik bagi Topik Diod Berdasarkan Domain Psikomotor - Mohd Zaki, Dayangku Nor Aisyah; Ab Rahman, Azmanirah (Research and Innovation in Technical and Vocational Education and Training, 2025)
The aim of this study is to determine the level of skill in performing practical electronics tasks for the topic of diodes based on the psychomotor domain. The research approach is quantitative. The study was conducted at the Faculty of Technical and Vocational Education, UTHM, involving 26 students taking the Electronics course. Two research instruments were used: a practical instruction paper and a checklist developed by the researcher baseThe purpose of this study is to determine the level of skill in performing electronic practicals on the topic of Diodes based on the psychomotor domain.  The research approach is quantitative.  The study was conducted at the Faculty of Technical and Vocational Education, UTHM on 26 students who are taking the Electronics course.  Two research instruments were used, namely the practical instruction sheet and the checklist developed by the researcher based on five levels in the advanced psychomotor domain, which are recognition of tools and materials, handling of tools and materials, basic operation of tools, competant operation of tools, and expert operation of tools.  The advanced psychomotor domain by Ferris and Aziz (2005) is considered appropriate because it develops competencies for practical skills and has seven levels to identify the psychomotor skill levels of students.  The content of the checklist has been validated by experts.  Data was analyzed using percentages.  The study findings indicate that students' skills in identifying equipment and materials are at a high level but decrease as the difficulty of the skills increases.  Early initiatives and actions need to be taken so that the students produced can meet the employers' demands in the job market.d on five levels in the advanced psychomotor domain, namely recognition of tools and materials, handling of tools and materials, basic operation of tools, competent operation of tools, and expert operation of tools. The content of the checklist was validated by experts. Data were analyzed using percentages. The findings revealed that students' skills at the level of identifying equipment and materials were high but decreased with increasing difficulty of the skills.